PEMANFAATAN SISTEM INFORMASI NOWCASTING DALAM MITIGASI BENCANA HIDROMETEOROLOGI - Erian Tasa; Shendyko Wicaksono; Nurdin Wibowo; Fahmi Khoirul Ichsan; Ceppy Multi Anggara; Any Widyawati; Farid Faisal; Tukiyat (Abdi Jurnal Publikasi, 2025)
Bekasi City, West Java Province, possesses a high vulnerability to hydrometeorological disasters, particularly floods, resulting from factors such as high rainfall, land-use change, and topographical conditions involving large rivers. Currently, the monitoring system used by the Bekasi City BPBD (Regional Disaster Management Agency) still relies on CCTV and manual observation, which have limitations in automation, data integration, and response speed. To address this, the utilization of information technology, such as the Internet of Things (IoT) and Nowcasting systems, offers a solution for more responsive and real-time disaster mitigation. Nowcasting, as a precise short-term weather forecasting method, combines radar data, satellite imagery, and field observations to enhance the accuracy of extreme weather predictions. This research aims to introduce the application of IoT and radar technology within the disaster mitigation system in Bekasi City to improve the effectiveness of the early warning system and support rapid decision-making. Through community service activities, Master's students in Informatics Engineering from Pamulang University presented material on the implementation of Nowcasting and a water level monitoring system based on radar sensors and IoT. This activity also demonstrated the potential for developing predictive flood models using machine learning, such as Long Short-Term Memory (LSTM). The results indicate that integrating these systems can significantly enhance early flood detection capabilities. The collaboration between Pamulang University and the Bekasi City BPBD serves as a model of strategic synergy for disaster mitigation innovation.